Local governance role in provincial development in Vietnam - Quynh Nguyen, Huy (Edelweiss Applied Science and Technology, 2024)
Improving public governance efficiency and effectiveness plays an important role in economic development. But research shows this relationship to be highly dependent on the country context. This paper analyzes the role of local governance on provincial economic development in Vietnam. Results show that the good governance has a positive relationship with the economic size of provinces andper capita income and contributes to poverty reduction. If the local governace index increases by 10%, the per capita income will increase by 4.38% and the poverty rate will decrease by 8%. Analysis also shows that control of corruption, grassroot citizen participation, accountability and transparency, and improvement of public administrative procedures impact poverty reduction, with corruption control having a negative correlation coefficient. Thus, effectiveness of local governance correlates with provincial economic developmentin Vietnam.